Saliva 1, 5-anhydroglucitol is associated with early-phase insulin secretion in Chinese patients with type 2 diabetes. Issue 1 (24th June 2021) - Ying, Lingwen; Jian, Chaohui; Ma, Xiaojing; Ge, Kun; Zhu, Wei; Wang, Yufei; Zhao, Aihua; Zhou, Jian; Jia, Wei; Bao, Yuqian
Abstract : Introduction: Saliva collection is a non-invasive test and is convenient. 1, 5-anhydroglucitol (1, 5-AG) is a new indicator reflecting short-term blood glucose levels. This study aimed to explore the relationship between saliva 1, 5-AG and insulin secretion function and insulin sensitivity. Research design and methods: Adult patients with type 2 diabetes who were hospitalized were enrolled. Based on blood glucose and C-peptide, homeostasis model assessment 2 for β cell secretion function, C-peptidogenic index (CGI), △2-hour C-peptide (2hCP)/△2-hour postprandial glucose (2hPG), ratio of 0–30 min area under the curve for C-peptide and area under the curve for glucose (AUCCP30 /AUCPG30 ), and AUC2hCP /AUC2hPG were calculated to evaluate insulin secretion function, while indicators such as homeostasis model assessment 2 for insulin resistance were used to assess insulin sensitivity. Results: We included 284 subjects (178 men and 106 women) with type 2 diabetes aged 20–70 years. The saliva 1, 5-AG level was 0.133 (0.089–0.204) µg/mL. Spearman's correlation analysis revealed a significantly negative correlation between saliva 1, 5-AG and 0, 30, and 120 min blood glucose, glycated hemoglobin A1c, and glycated albumin (all p<0.05), and a significantly positive association between saliva 1, 5-AG and CGI ( r =0.171, p=0.004) and AUC CP30 /AUC PG30 ( r =0.174, p=0.003). The above correlations still existed after adjusting for age, sex, body mass index, and diabetes duration. In multiple linear regression, saliva 1, 5-AG was an independent factor of CGI (standardized β =0.135, p=0.015) and AUC CP30 /AUC PG30 (standardized β =0.110, p=0.020). Conclusions: Saliva 1, 5-AG was related to CGI and AUCCP30 /AUCPG30 in patients with type 2 diabetes. Trial registration number: ChiCTR-SOC-17011356.